Komunikasi Dakwah Persuasif dengan Metode Story Telling - Siti Lutfi Latifah; Siti Aminah; Gita Puspita (Da'watuna: Journal of Communication and Islamic Broadcasting, 2022)
This study aims to determine the persuasive da'wah communication strategy of Kak Syaf and Chiko by using the story telling method. The research method used is descriptive method with a qualitative approach. The theory used is reinforcement theory by Hovlan, Janis and Kelly in 1976. The results of this research are Kak Syaf's da'wah communication strategy using story telling focusing on three strategic stages, namely: (1) namely attracting mad'u's attention by playing music that is friendly to them after the music is played, dolls are presented which are used as media for Kak Syaf's da'wah named Chiko. (2) given religious understanding using the story telling method or fairy tales and then reinforced with games that support the da'wah messages conveyed, after that strategy (3) namely the acceptance stage by making a good impression that leaves an impression on children, one of the ways is to issue a magic book in the book there is a gift that has been prepared. Keywords: Communication, Dakwah, Story telling